Learning and its relation to human development in primary classes: contributions of the Zankov’s System - Guseva, Liudmila Grigorievna; Martins, Iury Kesley Marques de Oliveira (Obutchénie. Revista de Didática e Psicologia Pedagógica, 2023)
Different developmental didactic systems gained prominence from 1950 onwards in the Post-Soviet states, based on the dialectic relationship between learning and development signaled by Lev Vygotsky and his collaborators. This text aims to present the fundamentals of the Zankov System, with emphasis on the pedagogical work aimed at the zone of possible development in the context of elementary education. This system is the synthesis of different theoretical and empirical research carried out by Zankov and his research group, which allowed the understanding of a concrete method for educational processes in primary grades. In this scenario, the work of teachers is based on five inseparable principles: teaching at an optimal level of difficulty, emphasizing theoretical knowledge, proceeding at a rapid pace, developing student’s awareness of the learning process and the purposeful, systematic development of each student. These principles are presented throughout the text from examples from the teaching about mathematics and natural sciences. Finally, the pedagogical contribution of the Zankov System and its potential for different experiences in basic education are highlighted.